Contribution of videothoracoscopy in the management of thoracic wounds with diaphragmatic lesions: A single African center experience. (April 2020) - Rabiou, Sani; Harmouchi, Hicham; Lakranbi, Marouane; Rachid, Sani; Ouadnouni, Yassine; Smahi, Mohamed
Background and aims: The management of thoracic wounds induced by sharp objects outside an extreme emergency remains controversial. The means vary from exploratory thoracotomy to simple monitoring. Between these two extremes, videothoracoscopy as a means of exploration plays an important role and helps to avoid unnecessary thoracotomies, thus making it possible to make early diagnosis of diaphragmatic lesions. The aim of this study was to report our experience in videothoracoscopic management of thoracic wounds by penetrating objects. Material and methods: From January 2010 to December 2015, 58 patients with an average age 22.5 years with a thoracic stab wound with a stable hemodynamic condition underwent videothoracoscopy. Results: Thoracoscopy revealed a diaphragmatic injury in 17 patients, cardiac or pericardial wounds in four and a haemorrhagic pulmonary injury in 1; all were treated at video-assisted mini-thoracotomy. In the other 36 patients, videothoracoscopic exploration did not demonstrate any intra-thoracic lesion and the procedure consisted of aspiration of a residual hemothorax with the installation of a good view-controlled thoracic drainage. Hospital stay was between 48 and 72 h. Conclusion: Videothoracoscopy is a safe and effective way to explore the thoracic cavity in patients with chest wounds with suspected diaphragmatic lesions. It avoids thoracotomy especially in hemodynamically stable patients.